Bond-slip behavior between high-strength steel tube and Ultra-high Performance Concrete. (January 2023) - Cao, Xuan; Xie, Xiang-Dong; Zhang, Tian-Yi; Du, Guo-Feng
Abstract: To satisfy the requirement of super high-rise buildings and large-span structures, an Ultra-high Performance Concrete Filled High-Strength Steel Tube (UHPC-FHSST) is presented. The effects of concrete strength, length-to-diameter ratio, and diameter-to-thickness ratio on interfacial bond-slip performance are investigated through push-out tests of 12 UHPC-FHSST specimens. The bond-slip process of the UHPC-FHSST is revealed and its strain evolution is analyzed. The research results show that the bond strength between the high-strength steel tube (HSST) and the UHPC core increases with the decrease of the diameter-to-thickness ratio and the length-to-diameter ratio, and the increase of concrete strength will lead to the decrease of bond strength. The longitudinal strain increases with the growth of the axial load. Based on the experimental results, the shear transfer length is determined and computed, and the mathematical model to reflect the bond-slip behavior of UHPC-FHSST is developed, which can provide valuable instruction for the engineering application of UHPC-FHSST.